The Development and Validation of a Direct LC-MS/MS Assay for the Determination of Tenofovir-diphosphate in Dried Blood Spots for the Analysis of Clinical Samples - Oberholster, Lucas (Division of Clinical Pharmacology, 2020)
Tenofovir (TFV) and emtricitabine (FTC) are nucleoside reverse transcriptase inhibitors, often used in preexposure prophylaxis (PrEP) trials: where antiretroviral drugs are administered to high-risk, HIV-negative individuals to prevent HIV infection. Both drugs are safe when taken either daily or intermittently, which is ideal for PrEP regimens where adherence may not be high. The minimum number of doses estimated to confer high PrEP efficacy for a TFV/FTC regimen is four or more doses per week, resulting in a 95% lower risk of HIV acquisition. However, this is highly dependent on various host factors, of which adherence plays the largest role. The aim of the project was to develop a novel sensitive, specific, and robust direct method for the measurement of adherence, utilising tenofovir-diphosphate (TFV-DP) in dry blood spots (DBS) through LC-MS/MS analysis, to replace the current costly and laborious indirect method currently used to elucidate adherence of patients. This indirect method faces challenges, due to the polar nature of TFV and its metabolites, leading to separation and retention issues. The existing method applied a technique which separated the parent drug from the metabolite and then back-converted all metabolites to the parent drug before analysing the samples on LC-MS/MS. The developed alternative method aimed to reduce the time taken for each assay and the associated cost of consumables. TFV-DP is a highly polar compound and traditional reverse-phase chromatography has poor retention and separation capabilities when used to retain polar compounds, therefore alternative strategies were implemented. In this developed direct method, an anion exchange column was used along with a pH gradient, with the aim of improving separation and chromatography of TFV, TFV-DP, and tenofovir-monophosphate (TFV-MP). The method was optimised and validated using current U.S. Food and Drug Administration (FDA) and European Medical Agency (EMA) guidelines. The use of the anion exchange column resulted in a marked increase in retention time and allowed baseline separation of TFV, TFV-DP, and TFV-MP. Determination of TFV-DP from DBS was performed using three 3 mm DBS punches per sample, which underwent an extraction procedure followed by high-performance liquid chromatography with tandem mass spectrometry detection on an AB Sciex Qtrap 5500 mass spectrometer. The transitions of the protonated precursor ions were monitored at m/z 448.0 and 452.9 to the product ions m/z 350.0 and 354.9 for TFV-DP and the deuterated TFVDP internal standard, respectively. The method was validated over a range of 50–6400 fmol/punch for TFV-DP. The developed direct method had a lower limit of quantification (LLOQ) of 50 fmol/punch, which was higher than that of the indirect method; therefore, it had less sensitivity. The reduced sensitivity was acceptable, since the methods were meant for the measurement of adherence. The direct method had an ULOQ of 6400 fmol/punch, which was similar to that of the indirect method. The direct method also required significantly less on-bench sample processing and, therefore, was less time consuming and costly. To determine the suitability and accuracy of the direct method in comparison to the indirect method a comparative analysis was completed by analysing the same samples using both the indirect and direct method. The developed method met all the validation requirements and a strong correlation was observed between the results of the indirect and direct methods during the comparative analysis.